Promoting digital technology for labour leaders training in Nigeria: issues and perspectives (2022)
Labour union leaders are very important to the success of any union activities. The labour leaders are expected to drive their members towards the achievement of the various goals set by the union. These leaders therefore need the necessary leadership skills to enable them lead effectively. Hence, the need for regular training programs to equip them with adequate skills such as. empathy, communication, problem solving, creativity, interpersonal and team work. However, such regular training programmes aimed at equipping, building and enhancing union leaders’ capacity may not be possible due to constraints like time and finance. The break out of COVID-19 which ravaged the whole world has also served as a deterrent to physical training or gathering of people in large numbers. In order to overcome these barriers, there is a call to promote digital industrial training programmes for the labour leaders through the principles of Adult Education. This paper examined the rationale and perspectives for promoting digital industrial training programmes among labour union leaders in Nigeria.